The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acssuschemeng.0c03861
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Vacancy-Rich Cubic CeO2 Nanowires as Catalysts for Vanadium Redox Flow Batteries

Abstract: A novel, low-cost, and powerful cerium-oxide nanowire (CeO2NW) electrode decorated with graphite felt (GF) through a one-step hydrothermal method was proposed in this study. Subsequently, hydrogen annealing was conducted to create defective-hydrogen-annealed CeO2NWs decorated with GF (H–CeO2NWs–GF) for use in vanadium redox flow batteries (VRFBs). The electrochemical results show that the H–CeO2NWs–GF reveals excellent electrocatalytic effects toward the VO2 +/VO2+ redox process in VRFBs at the positive electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Regarding metal catalysts [e.g., Cu (Wei et al, 2016), Ir (Wang et al, 2007) and Sb (Kou et al, 2020)], Zhou et al (2020) used semi-embedded carbon felt with bismuth nanospheres, which had good catalytic activity and could effectively promote the redox reaction of the negative electrode. For metal oxides [e.g., Nd 2 O 3 (Fetyan et al, 2018), MnO 2 (Ma et al, 2018), and PbO 2 (Wu et al, 2014)], Bayeh et al (2020) (Etesami et al, 2018)], Park et al (2013) demonstrated that carbon nanofiber/nanotube composite catalysts had good electrocatalytic performance in VRFB. Compared with the untreated electrode, the discharge capacity of the modified electrode increased by 64% at 40 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding metal catalysts [e.g., Cu (Wei et al, 2016), Ir (Wang et al, 2007) and Sb (Kou et al, 2020)], Zhou et al (2020) used semi-embedded carbon felt with bismuth nanospheres, which had good catalytic activity and could effectively promote the redox reaction of the negative electrode. For metal oxides [e.g., Nd 2 O 3 (Fetyan et al, 2018), MnO 2 (Ma et al, 2018), and PbO 2 (Wu et al, 2014)], Bayeh et al (2020) (Etesami et al, 2018)], Park et al (2013) demonstrated that carbon nanofiber/nanotube composite catalysts had good electrocatalytic performance in VRFB. Compared with the untreated electrode, the discharge capacity of the modified electrode increased by 64% at 40 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding metal catalysts [e.g., Cu (Wei et al, 2016 ), Ir (Wang et al, 2007 ) and Sb (Kou et al, 2020 )], Zhou et al ( 2020 ) used semi-embedded carbon felt with bismuth nanospheres, which had good catalytic activity and could effectively promote the redox reaction of the negative electrode. For metal oxides [e.g., Nd 2 O 3 (Fetyan et al, 2018 ), MnO 2 (Ma et al, 2018 ), and PbO 2 (Wu et al, 2014 )], Bayeh et al ( 2020 ) modified GF with cubic CeO 2 nanowires and used it as a catalyst for VRFB. This resulted in abundant defects on the electrode surface and increased active sites, meaning that the CeO 2 nanowires could significantly improve the /VO 2+ redox process.…”
Section: Introductionmentioning
confidence: 99%
“…Pure MgO without the addition of CeO 2 (Ce:Mg = 0:100) exhibited distinct XRD reflections corresponding to a cubic lattice with (111), (200), and (220) planes (hkl indices in black in Figure 1A) [29]. As the amount of Ce precursor increased in the synthesis gel composition, with a corresponding decrease in Mg precursor, the XRD peak intensities for MgO decreased gradually, and the XRD reflections corresponding to the cubic structure of CeO 2 , with different lattice parameters, became more prominent (hkl indices in red in Figure 1A) [30]. The mixed phases of CeO 2 and MgO with controlled gel composition during synthesis were characterized by the Rietveld refinement, which quantitatively analyzed the composition ratio of CeO 2 and MgO as summarized in Table 1 [31][32][33][34].…”
Section: Effect Of Composition In Ceo 2 -Mg(oh) 2 Supporting Au Nanoparticlesmentioning
confidence: 99%
“…However, these noble metals have lower elemental abundance and higher costs. To diminish the costs, cheap metal oxides such as Nb 2 O 5 [8], Ta 2 O 5 [9], W 18 O 49 [10], and CeO 2 [11] have been studied and exhibited good electrocatalytic activity. However, since the transition metal cations present several oxidative states, they make oxidation and reduction reactions carry on poor electronic conductivity and hinder the charge transfer efficiency from the catalysts to electrodes.…”
Section: Introductionmentioning
confidence: 99%